COMPUTER SUPPORT OF THE PROCESS OF SPECIALTY COMPETENCE FORMING OF FUTUR NAVIGATOVS WHILE STUDYING “SPHERICAL TRIGONOMETRY” - Dzhezhul, T.C. (Journal of Information Technologies in Education (ITE), 2010)
The article is devoted to the questions of forming of informative competences with the use of informative of communication technologies for the students of marine institute on the example of theme «Spherical trigonometry» - as a mathematical vehicle of disciplines of skipper cycle.